2020
DOI: 10.1155/2020/6909672
|View full text |Cite
|
Sign up to set email alerts
|

INHBB Is a Novel Prognostic Biomarker Associated with Cancer-Promoting Pathways in Colorectal Cancer

Abstract: Background. Inhibin subunit beta B (INHBB) is a protein-coding gene that participated in the synthesis of the transforming growth factor-β (TGF-β) family members. The study is aimed at exploring the clinical significance of INHBB in patients with colorectal cancer (CRC) by bioinformatics analysis. Methods. Real-time PCR and analyses of Oncomine, Gene Expression Omnibus (GEO), and The Cancer Genome Atlas (TCGA) databases were utilized to evaluate the INHBB gene transcription level of colorectal cancer (CRC) tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 34 publications
(34 reference statements)
2
17
0
Order By: Relevance
“…As a proteincoding gene, inhibin subunit beta B (INHBB) is involved in the synthesis of transforming growth factor-β (TGF-β) family members. INHBB expression has been found to be upregulated in colorectal cancer tissues and to be positively related to stromal and immune scores (Yuan et al, 2020). High RBP7 expression has been confirmed to be an independent biomarker for poor cancer-specific survival in patients with late-or early-stage colon cancer.…”
Section: Discussionmentioning
confidence: 94%
“…As a proteincoding gene, inhibin subunit beta B (INHBB) is involved in the synthesis of transforming growth factor-β (TGF-β) family members. INHBB expression has been found to be upregulated in colorectal cancer tissues and to be positively related to stromal and immune scores (Yuan et al, 2020). High RBP7 expression has been confirmed to be an independent biomarker for poor cancer-specific survival in patients with late-or early-stage colon cancer.…”
Section: Discussionmentioning
confidence: 94%
“…As a protein-coding gene, inhibin subunit β B (INHBB) is involved in the synthesis of transforming growth factor- β (TGF- β ) family members. Yuan et al found that overexpression of INHBB largely contributed to macrophage infiltration and impeded the infiltration of memory T cells, mast cells, and dendritic cells in colorectal cancer and was correlated with worse OS and DFS [ 40 ]. According to Chen et al [ 41 ], the growth and metastasis of an orthotopic hepatocellular carcinoma (HCC) tumor were promoted by the Sox9/INHBB axis, which activated peritumoral hepatic stellate cells (HSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibin subunit beta B gene ( INHBB ) encodes a pre-protein, which subsequently is processed to inhibin and activin [ 86 ]. Inhibin protein consists of a heterodimer formed by the two subunits α and β, which are secreted by ovarian granulosa cells and testicular Sertoli cells [ 162 ].…”
Section: Novel Methylation Biomarkers In Crc and Metastasis Prognosismentioning
confidence: 99%
“…In fact, INHBB is hypermethylated in CRC, and its expression was negatively correlated with methylation. Furthermore, the overexpression of INHBB is significantly and positively associated with invasion depth, distant metastasis, and CRC stage [ 86 , 167 ].…”
Section: Novel Methylation Biomarkers In Crc and Metastasis Prognosismentioning
confidence: 99%